Implementation of Caterpillar Pest Control (CPC) on Solar Cell Based Onion Plants to Increase Productivity - Wahyu Tri Handoko; Moh. Zainul Falah; Dhiyaurrahman Fakhruddin; Muhammad Sadidul Itqon; Langlang Gumilar; Farah Wardatul Afifah (Bulletin of Community Engagement, 2024)
One of the agricultural products that is very necessary as a cooking spice is onions. Onions are a mandatory spice in every dish to add flavor and enjoyment to the dish. Onion plants are not limited to the season at which they are planted so farmers can plant onions at any time, especially shallots. Based on this, one of the Farmer Groups in Krejengan District, Probolinggo Regency, is a forum for deliberation regarding agriculture, especially shallots. In shallot farming in Krejengan District, in dealing with caterpillar and planthopper pests, chemical pesticides are often used excessively. This certainly hurts the health of those who consume shallots and the environmental impact. On the other hand, spraying chemical pesticides has large costs in purchasing pesticides and farmer labor. If this is not done, it will have an impact on reducing shallot crop production and even result in crop failure. This community service activity program aims to reduce the use of chemical pesticides for pest control, which of course can reduce the costs of purchasing pesticides and farmer labor. Apart from that, by reducing the use of chemical pesticides, those who consume shallots are healthier. By doing this, the Agro Makmur Farmers Group can maintain the shallot production yields by creating a pest control device or Caterpillar Pest Control (CPC) for solar cell-based shallot plants so that it is environmentally friendly.